Impact of Burdizzo and Surgical Castration on Immune and Oxidative Stress Markers in Cattle - Thanyakorn Chalalai; Piyarat Srinontong; Worapol Aengwanich; Kanticha Srisila; Sudarat Promkrathok; Mookdawan Sununta; Bhuripit Saraphol; Zhiliang Wu (Veterinary Sciences)
Castration is an essential procedure in beef cattle management, designed to enhance meat quality, regulate aggressiveness, and control undesirable breeding. This study compared the impacts of Burdizzo and surgical castration on the immunological, oxidative, and inflammatory responses in Angus calves. Calves were randomly assigned to the Burdizzo (n = 4) and surgical (n = 4) castration groups. Blood samples were collected before castration and 3, 6, 24, and 48 h post-castration for the measurement of the pro-inflammatory cytokines TNF-α and IFN-γ, the anti-inflammatory cytokine IL-10, the oxidative stress markers malondialdehyde and nitric oxide, the total antioxidant capacity, and peripheral blood mononuclear cell populations, including CD3+CD4+, CD3+CD8+, and CD3+WC1+ T-cells. The results showed that Burdizzo castration caused significantly higher levels of IFN-γ at 3 and 6 h, TNF-α at 24 and 48 h, IL-10 at 3 and 24 h, and malondialdehyde at 24 h post-castration (p < 0.05), indicating more intense inflammatory and oxidative stress responses. Both methods caused alterations in CD3+CD4+ and CD3+CD8+ T-cell counts, while Burdizzo castration induced longer-lasting immune activation. These findings indicate that surgical castration may provide welfare advantages by mitigating prolonged inflammation and stress and promoting faster recovery. This study offers insights into optimal castration practices prioritizing productivity and animal welfare.